2018
DOI: 10.1093/nar/gkx1277
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of recombination suppression in the hybrid between Caenorhabditis briggsae and C. nigoni

Abstract: DNA recombination is required for effective segregation and diversification of genomes and for the successful completion of meiosis. Recent studies in various species hybrids have demonstrated a genetic link between DNA recombination and speciation. Consistent with this, we observed a striking suppression of recombination in the hybrids between two nematodes, the hermaphroditic Caenorhabditis briggsae and the gonochoristic C. nigoni. To unravel the molecular basis underlying the recombination suppression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…As a biomedical model organism, the free-living soil nematode Caenorhabditis elegans is the first model nematode, and the first eukaryotic animal ever had its whole genome sequenced (The Caenorhabditis elegans Sequencing Consortium 1998). Other free-living nematodes had their genome sequenced subsequently in the last two decades (Stein et al 2003;Dieterich et al 2008;Kanzaki et al 2018;Ren et al 2018;Yin et al 2018;Stevens et al 2019;Weinstein et al 2019). Aside from C. elegans, Pristionchus pacificus is the only satellite model nematode with advanced functional genomic resources, bioinformatics and genetic tools (Rödelsperger et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a biomedical model organism, the free-living soil nematode Caenorhabditis elegans is the first model nematode, and the first eukaryotic animal ever had its whole genome sequenced (The Caenorhabditis elegans Sequencing Consortium 1998). Other free-living nematodes had their genome sequenced subsequently in the last two decades (Stein et al 2003;Dieterich et al 2008;Kanzaki et al 2018;Ren et al 2018;Yin et al 2018;Stevens et al 2019;Weinstein et al 2019). Aside from C. elegans, Pristionchus pacificus is the only satellite model nematode with advanced functional genomic resources, bioinformatics and genetic tools (Rödelsperger et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The publication of the C. briggsae genome in 2003 enabled the first comparative genomics studies of Caenorhabditis, which revealed an unusually high rate of intrachromosomal rearrangement but comparatively rare interchromosomal rearrangement (Stein et al 2003). Additional genome sequences have been published from species across the genus (Mortazavi et al 2010;Fierst et al 2015;Slos et al 2017;Kanzaki et al 2018;Ren et al 2018;Yin et al 2018). Comparisons between genomes of hermaphroditic species such as C. elegans and their outcrossing relatives have exposed the genomic consequences of a switch in reproductive mode from gonochorism to autogamous hermaphroditism, including changes in overall genome structure, gene structure, and protein-coding gene content (Thomas et al 2012;Fierst et al 2015;Kanzaki et al 2018;Yin et al 2018).…”
mentioning
confidence: 99%
“…Intriguingly, Drosopphila genes translocated from autosome to the Y Chromosome are undergoing rapid degeneration and pseudogenization, suggesting a differential selection pressure of bidirectional gene translocation between the autosome and the X Chromosome. Given that the size of the hermaphroditic C. briggsae genome is substantially smaller than that of the dioecious C. nigoni and [41,42], and other Caenorhabditis species [43], it remains to be determined whether differential gene translocation exists between the X Chromosome and the autosomes between the two species, which is responsible for the observed X-autosome interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Rescue of the male sterility caused by zzyIR10330 would be indicative of the two loci. It is worth noting that the genomic sequences between C. briggsae and C. nigoni diverge substantially from each other in both sequence identity and size [41,44], which significantly inhibits DNA recombination frequency. Selective loss of male-specific genes in hermaphroditic species and its subsequent reinforcement further complicates the precise mapping of HI loci using backcrossing.…”
Section: Discussionmentioning
confidence: 99%